A cultural perspective on knowledge management: The success story of Sarkuysan company - (:unkn) unknown (My University, 2008)
Purpose - The purpose of this paper is to demonstrate how effective knowledge management practices combined with a unique corporate culture have enabled the company Sarkuysan to cope with the challenges it has faced throughout the years and made it an extremely successful company. Design/methodology/approach - A company case was chosen to explain the influences of cultural determinants on the success of knowledge management. This objective was achieved by conducting several interviews with the top managers of the company. Findings - The findings of the article are, that effective knowledge management practices combined with a unique corporate culture can enable companies to instill a lasting knowledge management culture. Research limitations/implications - The article is based on a case study, which limits the possibility of making general conclusions. Whereas many studies discuss knowledge management primarily as an IT problem, this study focuses on the topic as a cultural issue. Practicalimplications - Most current literature on knowledge management deals with multinational companies with Western management structures. This article describes how knowledge management is applied in an emerging market context, which does not necessarily share the culture, structures and ideals of the organizations on which current theories are based. Originality/value - This article focuses on the concept of knowledge as a cultural issue, rather than a problem that can be solved by sophisticated information technology infrastructures. The paper deals with a firm from an emerging market/country, i.e. Turkey.
Keywords: Business continuity; Companies; Knowledge management; Storytelling; Turkey